Fixed-time sliding mode tracking control for autonomous underwater vehicles. (December 2021) - Zheng, Jiaqi; Song, Lei; Liu, Lingya; Yu, Wenbin; Wang, Yiyin; Chen, Cailian
Abstract: In this paper, a fixed-time sliding mode controller (FSMC) with disturbance observer (DO) is proposed to solve the trajectory tracking control problem for autonomous underwater vehicles (AUVs) under time-varying external disturbances. Firstly, by using the sliding mode control method, an FSMC is proposed for reducing the tracking errors. Secondly, considering the estimation problem of time-varying disturbances, a fixed-time DO is designed to reconstruct the information of the AUV. Finally, The DO can compensate time-varying disturbances and the FSMC can reduce the tracking errors incorporating the information from the DO. Thus, the FSMC-DO for AUV is derived. Compared with the conventional FSMC and the finite time controller, the proposed FSMC-DO not only offers a faster convergence rate but also a higher tracking accuracy and robustness for the trajectory tracking control of AUVs. Simulation results are provided to show the superior performance of the proposed FSMC-DO.